1997
DOI: 10.1152/jn.1997.78.4.1948
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which Cell Geometry Controls Repetitive Impulse Firing in Retinal Ganglion Cells

Abstract: Models for generating repetitive impulse activity were developed based on multicompartmental representations of ganglion cell morphology in the amphibian retina. Each model includes five nonlinear ion channels and one linear (leakage) channel. Compartmental distribution of ion channel type and density was designed to simulate whole cell recording experiments carried out in the intact retina-eyecup preparation. Correspondence between the model and physiology emphasized channel-specific details in the impulse wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
137
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(150 citation statements)
references
References 26 publications
13
137
0
Order By: Relevance
“…The estimated location of highest sensitivity to stimulation was 13 m from the soma along the path of the axon. This finding provides experimental support for the hypothesis that the site of activation during electrical stimulation is the axon hillock or the initial portion of the axon (Coombs et al, 1957;Wollner and Catterall, 1986;Fohlmeister and Miller, 1997;Schiefer and Grill, 2006;Sekirnjak et al, 2006).…”
Section: Axonsupporting
confidence: 67%
“…The estimated location of highest sensitivity to stimulation was 13 m from the soma along the path of the axon. This finding provides experimental support for the hypothesis that the site of activation during electrical stimulation is the axon hillock or the initial portion of the axon (Coombs et al, 1957;Wollner and Catterall, 1986;Fohlmeister and Miller, 1997;Schiefer and Grill, 2006;Sekirnjak et al, 2006).…”
Section: Axonsupporting
confidence: 67%
“…The differences we have observed in the intrinsic physiological properties of RGCs are ultimately attributed to many factors including their morphology (Fohlmeister and Miller 1997;Sheasby and Fohlmeister 1999) and the complement of ion channels expressed by each cell type. While our data cannot unambiguously identify which channels are present in each cell type, the intrinsic properties we have observed do allow us to predict the relative abundance of certain types of ion channels expressed.…”
Section: Discussionmentioning
confidence: 91%
“…Prior studies of RGC intrinsic properties have been largely limited to identifying individual ion channel types without regard to an individual cell's morphological type. Only a handful of studies have attempted electrophysiological recordings with complete anatomical reconstruction of each cell, and yet fewer studies have sampled the entire cell population (Fohlmeister et al 2010;Fohlmeister and Miller 1997; Ishida 1991;Liets et al 2003;Lipton and Tauck 1987;Margolis and Detwiler 2007;O'Brien et al 2002; Myhr 2008, 2011;Robinson and Chalupa 1997;Robinson and Wang 1998; Sheasby and Fohlmeister 1999; Sucher and Lipton 1992;Tabata and Kano 2002; Van Hook and Berson 2010;Wang et al 1997;Zeck and Masland 2007). Moreover, no study has yet compared intrinsic properties for morphologically similar cell types across different mammalian species.…”
mentioning
confidence: 99%
“…In simulations of pacemaking in GPe neurons, a graded reduction in Na ϩ channel density also produced a similar graded reduction in pacemaking rate, arguing that TTX was not preferentially blocking one type of channel. When it has been examined carefully, spike initiation appears to take place in either the AIS or the neighboring nodes (Colbert and Johnston, 1996;Fohlmeister and Miller, 1997;Stuart et al, 1997;Colbert and Pan, 2002;Clark et al, 2005;Palmer and Stuart, 2006;McCormick et al, 2007;Meeks and Mennerick, 2007). Localization studies have shown the AIS and axon nodes to be enriched in Nav1.6 channels Krzemien et al, 2000;Tzoumaka et al, 2000;Boiko et al, 2001Boiko et al, , 2003Wittmack et al, 2004).…”
Section: Most Gating Properties Of Gpe Namentioning
confidence: 99%